SPATIOTEMPORAL VARIATIONS OF SHORT-PERIOD S-WAVE ATTENUATION FIELD IN SOURCE ZONES OF LARGE AND GREAT EARTHQUAKES - Gordienko D.D.; Kopnichev Yu.F.; Sokolova I.N. (My University, 2006)
Attenuation field characteristics of shear waves in upper mantle in source zones of 34 large and great earthquakes worldwide were studied. Effective coda quality factor of Lg and Sn waves in two time intervals were determined. It is demonstrated that the period of 20 to 25 years following a large earthquake shows a regular decrease in attenuation in the uppermost mantle. This trend is most evident for events with normal and strike-slip faulting mechanisms. The revealed phenomena are attributed to ascent of mantle fluids into the crust following violent earthquakes.